Assessing the outcomes of anti-money laundering policies. Ambitions and reality - Slot, Brigitte; Swart, de Linette (Constructing and organising crime in Europe / Petrus C. van Duyne, Alexey Serdyuk, Georgios A. Antonopoulos, Jackie H. Harvey, Klaus von Lampe (Eds.); Kharkiv National University of Internal Affairs, Northumbria University, Teesside University, Utrecht University. – Chicago-Kharkiv : Eleven International Publishing, Kharkiv National University of Internal Affairs, 2019. - P. 399-415, 2019)
Боротьба з відмиванням грошей займає важливе місце в політичному порядку денному як на міжнародному рівні, так і в Нідерландах. Багато зусиль було направлено на запобігання відмиванню грошей, а також на виявлення і судове переслідування злочинців, які фактично витратили свої незаконно отримані гроші в легальній економіці. Міністерство юстиції Нідерландів замовило дослідження, щоб з'ясувати, наскільки діяльність і фактичні результати політики по боротьбі з відмиванням грошей в Нідерландах відповідають цілям політики по боротьбі з відмиванням грошей. В цьому розділі висвітлюються основні результати цього дослідження.

Combatting money-laundering ranks highly on the political agenda, both internationally and in the Netherlands. Much effort has been put into the prevention of money laundering, as well as detecting and prosecuting criminals who actually have spent their ill-gotten money in the legal economy. Not only has the legal framework been strengthened, e.g. the implementation of the fourth anti-money laundering directive and fine-tuning of the Dutch Penal Code, several financial programs have been introduced in order to strengthen the position of both the police and special investigators as well as the public prosecution. In addition, cooperation between the public and private sector is encouraged and several informal and formal networks combatting money laundering have been established. Anti-money laundering policies are part of the political agenda and many resources have been made available – both in terms of public money and human capacity. However, it is unknown what the impacts of these actions are on money laundering in particular and on crime in general. The Financial Action Task Force (FATF) has recently set-up a framework for assessing the effectiveness of anti-money laundering policies. In their fourth round of mutual evaluations, this new framework is applied for the first time. The mutual evaluation of the Netherlands is planned for 2020. In preparation of the coming mutual evaluation, the Dutch Ministry of Justice commissioned a study to investigate the extent to which the activities and the actual outcomes of the anti-money laundering policies in the Netherlands comply with the objectives of the anti-money laundering policies as formulated by the FATF. This chapter highlights the main outcomes of this exercise.

Борьба с отмыванием денег занимает важное место в политической повестке дня как на международном уровне, так и в Нидерландах. Много усилий было направлено на предотвращение отмывания денег, а также на выявление и судебное преследование преступников, которые фактически потратили свои незаконно полученные деньги в легальной экономике. Министерство юстиции Нидерландов заказало исследование, чтобы выяснить, насколько деятельность и фактические результаты политики по борьбе с отмыванием денег в Нидерландах соответствуют целям политики по борьбе с отмыванием денег. В этой главе освещаются основные результаты этого исследования.
Slot, Brigitte Assessing the outcomes of anti-money laundering policies. Ambitions and reality / Brigitte Slot, Linette de Swart // Constructing and organising crime in Europe / Petrus C. van Duyne, Alexey Serdyuk, Georgios A. Antonopoulos, Jackie H. Harvey, Klaus von Lampe (Eds.); Kharkiv National University of Internal Affairs, Northumbria University, Teesside University, Utrecht University. – Chicago-Kharkiv : Eleven International Publishing, Kharkiv National University of Internal Affairs, 2019. - P. 399-415. - DOI: https://doi.org/10.32631/ccc19.16.
Keywords: Constructing and organising crime in Europe; Materials of conferences. Збірники матеріалів наукових конференцій. Сборники материалов научных конференций; Наукові публікації. Scientific publications. Научные публикации; зарубіжний досвід; зарубежный опыт; foreign experience; Netherlands; Нидерланды; Нідерланди; отмывание денег; combatting money-laundering; money-laundering; боротьба з відмиванням грошей; відмивання грошей; борьба с отмыванием денег; Кримінологія. Criminology. Криминология